2020
DOI: 10.1038/s42004-020-0334-x
|View full text |Cite
|
Sign up to set email alerts
|

Spontaneous redox continuum reveals sequestered technetium clusters and retarded mineral transformation of iron

Abstract: The sequestration of metal ions into the crystal structure of minerals is common in nature. To date, the incorporation of technetium(IV) into iron minerals has been studied predominantly for systems under carefully controlled anaerobic conditions. Mechanisms of the transformation of iron phases leading to incorporation of technetium(IV) under aerobic conditions remain poorly understood. Here we investigate granular metallic iron for reductive sequestration of technetium(VII) at elevated concentrations under am… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 47 publications
3
5
0
Order By: Relevance
“…However, as equilibrium conditions were reached, the changes slowed, which is consistent with previous research where pristine iron has been shown to initiate relatively fast reductive removal, but as iron corrosion occurs on the particle surface resulting in the formation of iron oxide phases, electron transfer from the core of the iron is inhibited, leading to a slowdown in the removal process . The anticorrosive properties of both Cr­(VI) and Tc­(VII) minimize this effect as they passivate the surface, reducing corrosion reactions while also impacting the ability of ZVI to reduce contaminants on the surface. , …”
Section: Resultssupporting
confidence: 87%
See 4 more Smart Citations
“…However, as equilibrium conditions were reached, the changes slowed, which is consistent with previous research where pristine iron has been shown to initiate relatively fast reductive removal, but as iron corrosion occurs on the particle surface resulting in the formation of iron oxide phases, electron transfer from the core of the iron is inhibited, leading to a slowdown in the removal process . The anticorrosive properties of both Cr­(VI) and Tc­(VII) minimize this effect as they passivate the surface, reducing corrosion reactions while also impacting the ability of ZVI to reduce contaminants on the surface. , …”
Section: Resultssupporting
confidence: 87%
“…The XRD and SEM-EDS analysis indicated the incorporation of Tc into iron oxides, such as magnetite and goethite, which could potentially impede the reoxidation of Tc(IV). 14,33 Solid characterization reveals inhibited iron oxide formation in Tc(VII)-bearing samples, and larger concentrations of Cr(VI) lead to slower treatment rates. Although the concentration of Cr(VI) did not significantly influence the Tc(VII) reoxidation in this study, alterations in iron oxide formation could have implications for large-scale treatment processes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations